2019
DOI: 10.1123/jpah.2018-0317
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strength Training on Lipid and Inflammatory Outcomes: Systematic Review With Meta-Analysis and Meta-Regression

Abstract: Background: The aim of this study was to perform a systematic review with meta-analysis and meta-regressions evaluating the effects of isolated strength training (ST), compared with a control group, on total cholesterol (TC), triglycerides (TG), low-density (LDL), high-density lipoprotein (HDL), C-reactive protein (CRP), and adiponectin of adults. Methods: Embase, PubMed, Cochrane, and Scopus data sources were searched up to May 2017. Clinical trials that compared ST with a control group of adults older than 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 85 publications
5
24
0
11
Order By: Relevance
“…It is suggested that the effect of physical activity on PON activity is associated with the PON1-192 gene polymorphism 66 . Moreover, different age of the study population may also partly explain the differences between previous findings as this enzyme’s activity is very low at birth and increases with age 20 . The decrease in PON activity observed in our study’s endurance group may indicate increased lipid oxidation, which may be associated with a higher risk of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It is suggested that the effect of physical activity on PON activity is associated with the PON1-192 gene polymorphism 66 . Moreover, different age of the study population may also partly explain the differences between previous findings as this enzyme’s activity is very low at birth and increases with age 20 . The decrease in PON activity observed in our study’s endurance group may indicate increased lipid oxidation, which may be associated with a higher risk of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 72%
“…Several meta-analyses have shown a significant effect of both endurance and strength training on anthropometric and cardiometabolic parameters, providing evidence for reductions in body weight, body mass index (BMI), waist circumference, fat mass (FM), improved lipid profile, decreased glucose, insulin levels and blood pressure (BP) 16 20 . Although the benefits of endurance and strength training alone are well documented, studies comparing the effect of endurance and endurance-strength training on body composition and cardiometabolic markers have proved inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the RT program, no effects were observed on any of the cardiovascular risk parameters when comparing trained groups to untrained groups, although circulating levels of Total chol, LDL-chol and HDL-chol were decreased in the P+RT group, and both trained groups revealed a decrease in TG. Despite the recent meta-analyses describing beneficial effects of RT on circulating lipid levels in adults [ 15 , 85 ], multiple trials investigating RT effects on blood lipid levels observed no effects in postmenopausal women and older adults [ 19 , 21 , 68 , 86 ]. Thus, several studies have assessed this question by examining the individual response to RT in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle strength can be improved by muscle-strengthening activities, and resistance training, a typical muscle-strengthening activity, promotes decreases in TC, TG, and LDL-C levels and increases in HDL-C level. 32 In addition, skeletal muscle is a main tissue of fatty acid uptake and oxidation. 33 Taken together, grip strength may be a risk marker of the incidence of dyslipidemia and its components.…”
Section: Discussionmentioning
confidence: 99%